Automação de sistema de irrigação em malha fechada utilizando rede sem fio de sensores capacitivos de umidade do solo - Vasconcelos, Henrique Souza (2013)
Irrigation is one of the most influencing practices on agricultural production, requiring a high water consumption, which is a scarce resource critical to life’s preservation. Thus, techniques aimed at reducing energy and water waste by an irrigation system have been studied and applied under the name of precision irrigation. The main objective of this paper was to develop an automatic closed loop irrigation system based on the measurement of soil moisture by FDR capacitance sensors. An automatic irrigation systems allows a control which is far more precise than manual control, allowing fast and accurate decisions about how much and when to irrigate. For this to be possible, it was necessary to build electronic devices in order to read sensors in the crop field and control different points of the system: pumping house and hydraulic valves. A wireless sensor network (WSN) was chosen for communication between these devices. It allows a quick installation, since you don’t have to pull cords from the controller to the sensors and actuators on the crop field. We developed an automation software in Java that monitors and coordinates the entire network, which is executed in a personal computer (PC). Based on sensor readings and data on the irrigation system, the algorithm computes for how long to water the soil, remotely activating water pumps and hydraulic valves. In addition, the software verifies and stores data about the hydraulic pressure at the pumping house, protecting it against mechanical damage. The automation system was assembled in the field in order to monitor and control soil moisture in a maize crop field, being successful in this task. Some software problems were solved as they arose, showing the need for maintenance of an automation system. Storing pressure and soil moisture sensor data in a database provides a history of soil water status, allowing further analysis and evaluation of the irrigation system.